2006
DOI: 10.1111/j.1744-7410.2006.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships within the tropical soft coral genera Sarcophyton and Lobophytum (Anthozoa, Octocorallia)

Abstract: Abstract. The alcyonacean soft coral genera Sarcophyton and Lobophytum are conspicuous, ecologically important members of shallow reef communities throughout the Indo-West Pacific. Study of their ecology is, however, hindered by incomplete knowledge of their taxonomy: most species cannot be identified in the field and the two genera cannot always be distinguished reliably. We used a 735-bp fragment of the octocoral-specific mitochondrial protein-coding gene msh1 to construct a phylogeny for 92 specimens identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 35 publications
5
60
0
2
Order By: Relevance
“…As the taxonomic status of S. glaucum is still far from being consensual (McFadden et al, 2006;Steinke et al, 2012), the corals used on this experiment were classified as Sarcophyton cf. glaucum.…”
Section: Experimental Designmentioning
confidence: 99%
“…As the taxonomic status of S. glaucum is still far from being consensual (McFadden et al, 2006;Steinke et al, 2012), the corals used on this experiment were classified as Sarcophyton cf. glaucum.…”
Section: Experimental Designmentioning
confidence: 99%
“…Although other mitochondrial gene regions, most notably the octocoral-specific mitochondrial mutS homolog (mtMutS, previously known as msh1), appear to be somewhat better barcodes for octocorals than the widely used cytochrome oxidase I (COI), both mitochondrial markers still only discriminate about 70-80 % of congeneric species (McFadden et al 2011). Despite their inability to separate some closely related species, however, the use of DNA barcodes in biodiversity surveys has already proven useful for detecting cryptic species in octocorals, taxa for which there is often a paucity of morphological characters available for taxonomy (McFadden et al 2006(McFadden et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the animal collected from a different place in the GBR and studied by Coll et al [13] preyed upon S. trocheliophorum , which is according to McFaddens and co-workers phylogenetic research [53] found in the different clade from the S. glaucum species complex (see Fig. 12).…”
Section: Discussionmentioning
confidence: 93%
“…The phylogenetic analysis by McFadden et al clearly showed that the relationship and systematics of the soft coral genus Sarcophyton is not resolved (see Fig. 12) [53]. S. glaucum seems to be a species complex with at least 6 different clades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation